JavaScript Program to print Fibonacci Series

Last Updated : 13 Dec, 2023

The Fibonacci sequence is the integer sequence where the first two terms are 0 and 1. After that, the next term is defined as the sum of the previous two terms.

The sequence Fn of Fibonacci numbers is defined by the recurrence relation:

Fn = Fn-1 + Fn-2 with seed values F0 = 0 and F1 = 1

Examples:

`Input : 5 Output : 8Input :8Output :34`

There are three methods to print the Fibonacci series, which are described below:

Table of Content

Approach 1: Using for loop

Example: This example uses for loop to print the Fibonacci series.

javascript

 `function` `fibonacci(num) {` `    ``let num1 = 0;` `    ``let num2 = 1;` `    ``let sum;` `    ``let i = 0;` `    ``for` `(i = 0; i < num; i++) {` `        ``sum = num1 + num2;` `        ``num1 = num2;` `        ``num2 = sum;` `    ``}` `    ``return` `num2;` `}`   `console.log(``"Fibonacci(5): "` `+ fibonacci(5));` `console.log(``"Fibonacci(8): "` `+ fibonacci(8));`

Output:

`Fibonacci(5): 3Fibonacci(8): 13`

Approach 2: Using while loop

Example: This example uses a while loop to print the Fibonacci series.

javascript

 `function` `fibonacci(num) {` `    ``if` `(num == 1)` `        ``return` `0;` `    ``if` `(num == 2)` `        ``return` `1;` `    ``let num1 = 0;` `    ``let num2 = 1;` `    ``let sum;` `    ``let i = 2;` `    ``while` `(i < num) {` `        ``sum = num1 + num2;` `        ``num1 = num2;` `        ``num2 = sum;` `        ``i += 1;` `    ``}` `    ``return` `num2;` `}`   `console.log(``"Fibonacci(5): "` `+ fibonacci(5));` `console.log(``"Fibonacci(8): "` `+ fibonacci(8));`

Output:

`Fibonacci(5): 3Fibonacci(8): 13`

Approach 3: using recursion

As we know that the nth Fibonacci number is the summation of n-1 and n-2 term and the n-1 term is the summation of n-2 and n-3 terms. So, to get the nth Fibonacci term we can follow fib(n)=fib(n-1)+fib(n-2) fib(n)=fib(n-2)+fib(n-3)+fib(n-3)+fib(n-4) …. fib(n)=fib(1)+fib(0)+fib(1)+fib(0)+fib(1)+fib(0)….fib(1)+fib(0) [terms containing sum of fib(1) and fib(0) fib(1)=0 fib(2)=1

Example: This example shows the use of the above approach.

javascript

 `function` `fibonacci(num) {` `    ``if` `(num == 1)` `        ``return` `0;` `    ``if` `(num == 2)` `        ``return` `1;` `    ``return` `fibonacci(num - 1) + fibonacci(num - 2);` `}` `console.log(``"Fibonacci(5): "` `+ fibonacci(5));` `console.log(``"Fibonacci(8): "` `+ fibonacci(8));`

Output:

`Fibonacci(5): 3Fibonacci(8): 13`

Previous
Next